St. Catherine Orthodox parish in Vilnius in 1925-1936: the opposition flashpoint to the orthodox authority of Warszaw - Marcinkevičius, Andrius (Lietuvos istorijos studijos, 2004)
Last page with English resume missing.
Keywords: -